Effect of Cornelian Cherry (Cornus mas L.) Juice on Selected Quality Properties of Beef Burgers - Anna Marietta Salejda; Alicja Z. Kucharska; Grażyna Krasnowska (Journal of Food Quality)
Bioactive compounds of plant origin are becoming increasingly popular as food ingredients with a beneficial impact on human health. Therefore, the present study aimed to investigate the possibility of using different doses (0.5 g–1.5 g) of cornelian cherry juice (CCJ) as a functional additive in the production of beef burgers. Results of the experiment showed CCJ addition to cause high acidification of the meat emulsion and to decrease meat production yield was unbeneficial from the economic point of view. In contrast, the CCJ was highly effective in retarding lipid oxidation in beef burgers during storage wherein even a dose of 0.5 g CCJ resulted in beneficial inhibition of oxidative changes and at the same time had no negative effect on the sensory characteristics of beef burgers. CCJ can be applied in the meat industry to develop novel products; however, future research is needed regarding its acidifying properties.